When parents are incarcerated interdisciplinary research and interventions to support children - Haskins, Anna R.; Poehlmann-Tynan, Julie; Wildeman, Christopher James 1979- (APA Bronfenbrenner series on the ecology of human development, 2018)
"In this volume, prominent scholars across multiple disciplines examine how parental incarceration affects children and what can be done to help them. Sociologists, demographers, developmental psychologists, family scientists, and criminologists summarize the strongest research on the consequences of parental incarceration for children, with special attention to mediating and moderating variables. Scholars review policies and interventions that could lessen the likelihood of parental incarceration and/or help children whose parents have been imprisoned or jailed"--